2016
DOI: 10.53841/bpsecp.2016.33.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of working memory training programmes on children – a systematic review

Abstract: Background:An increasing body of evidence suggests that working memory can have a significant effect on the academic success of children in school (Gathercole & Alloway, 2008). As such a number of working memory training programmes have been developed and marketed commercially to schools and parents as tools for helping children to boost their working memory and as a result, their learning ability.Aim:The reliability and validity of this body of evidence has been challenged in recent years with questions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…This lack of transferable and durable effects might be attributed to such interventions training WM out of context and, therefore, ignoring potentially important contextual factors. Finally, recent reviews (see [65,66]) concluded that evidence that WM training leads to improvements in other areas, such as literacy and numeracy, is inconclusive at best, and further research is required to better understand the mechanisms through which WM training may improve WM and academic performance in children.…”
Section: Working Memory and Educationmentioning
confidence: 99%
“…This lack of transferable and durable effects might be attributed to such interventions training WM out of context and, therefore, ignoring potentially important contextual factors. Finally, recent reviews (see [65,66]) concluded that evidence that WM training leads to improvements in other areas, such as literacy and numeracy, is inconclusive at best, and further research is required to better understand the mechanisms through which WM training may improve WM and academic performance in children.…”
Section: Working Memory and Educationmentioning
confidence: 99%
“…Modul Intervensi Kognitif ini yang menggabungkan kemahiran membaca yang menumpukan kepada kemahiran dekoding dan berfokuskan kepada keupayaan kognitif dapat meningkatkan kecekapan membaca kepada murid yang berisiko dan Murid Berkeperluan Pendidikan Khas (MBPK) (Kendeou et al, 2014). Kajian-kajian terbaharu menunjukkan latihan atau intervensi memori kerja dapat meningkatkan kapasiti memori kerja dan berpotensi untuk peningkatan pembelajaran murid (Alloway et al, 2016;Randall & Tyldesley, 2016).…”
Section: Pengenalanunclassified
“…‫ـ2‬ M‫ـ‬ ‫ـ‬ ‫ـ`‬ ! ( ‫ـ-"‬ ‫أو‪ë‬‬ ‫ـ‬ C : Gray, et al (2012), Green (2014), McLaughlin (2016, Melby-Lervåg and Hulme (2013), Peijnenborgh, et al (2015), Prins, et al (2011), Randall and Tyldesley (2016…”
mentioning
confidence: 99%
“…-' ‫ـ‬ 1 ‫ت‬ ‫ـ‬ ‫أ"‬ ‫ر‬ Nelwan and Kroesbergen ( 2016 (Nelwan, et al 2018;Randall& Tyldesley, 2016) .…”
unclassified
See 1 more Smart Citation